Insight into the Mechanism of Salt-Induced Oxidative Stress Tolerance in Soybean by the Application of Bacillus subtilis: Coordinated Actions of Osmoregulation, Ion Homeostasis, Antioxidant Defense, and Methylglyoxal Detoxification - Mirza Hasanuzzaman; Md. Rakib Hossain Raihan; Farzana Nowroz; Masayuki Fujita (MDPI AG, 2022)
Considering the growth-promoting potential and other regulatory roles of bacteria, we investigated the possible mechanism of the role of Bacillus subtilis in conferring salt tolerance in soybean. Soybean (Glycine max cv. BARI Soybean-5) seeds were inoculated with B. subtilis, either through a presoaking with seeds or a direct application with pot soil. After 20 days of sowing, both the seed- and soil-inoculated plants were exposed to 50, 100, and 150 mM of NaCl for 30 days. A clear sign of oxidative stress was evident through a remarkable increase in lipid peroxidation, hydrogen peroxide, methylglyoxal, and electrolyte leakage in the salt treated plants. Moreover, the efficiency of the ascorbate (AsA)-glutathione (GSH) pathways was declined. Consequently, the plant growth, biomass accumulation, water relations, and content of the photosynthetic pigments were decreased. Salt stress also caused an increased Na+/K+ ratio and decreased Ca2+. On the contrary, the B. subtilis inoculated plants showed increased levels of AsA and GSH, their redox balance, and the activities of the AsA-GSH pathway enzymes, superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase, and peroxidase. The B. subtilis inoculated plants also enhanced the activities of glyoxalase enzymes, which mitigated methylglyoxal toxicity in coordination with ROS homeostasis. Besides this, the accumulation of K+ and Ca2+ was increased to maintain the ion homeostasis in the B. subtilis inoculated plants under salinity. Furthermore, the plant water status was uplifted in the salt treated soybean plants with B. subtilis inoculation. This investigation reveals the potential of B. subtilis in mitigating salt-induced oxidative stress in soybean plants through modulating the antioxidant defense and glyoxalase systems along with maintaining ion homeostasis and osmotic adjustments. In addition, it was evident that the soil inoculation performed better than the seed inoculation in mitigating salt-induced oxidative damages in soybean.